2018
DOI: 10.1007/s12262-018-1724-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Cystic Duct Stump Stone or Gall Bladder Remnant Stone

Abstract: Retained calculi in the cystic duct or gall bladder remnant can present as a post-cholecystectomy problem. Increased suspicion is necessary to diagnose this condition in a symptomatic post-cholecystectomy patient. Ultrasonography usually detects this condition, but magnetic resonance cholangiopancreatography is the test of choice for diagnosis as well as for surgical planning. Laparoscopic re-excision of the stump in most cases is feasible and safe. It is increasingly becoming the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Most recently, Kar et al published results on 12 patients with cystic duct and remnant gallbladder stones. While seven patients could be managed laparoscopically, five patients required conversion to an open procedure [28]. These studies demonstrate the lack of a viable minimally invasive surgical alternative for these patients.…”
Section: First Author (Year)mentioning
confidence: 89%
“…Most recently, Kar et al published results on 12 patients with cystic duct and remnant gallbladder stones. While seven patients could be managed laparoscopically, five patients required conversion to an open procedure [28]. These studies demonstrate the lack of a viable minimally invasive surgical alternative for these patients.…”
Section: First Author (Year)mentioning
confidence: 89%
“…In accordance with similar results from previously published studies, our data demonstrated that the conventional cystic duct anatomy (right lateral insertion at the mid-point between the confluence of the right/left hepatic ducts and the ampulla of Vater) was present only in fewer than 50% of our patients. Interestingly, fewer than 2% of our patients had incidental cystic duct stones [ 11 – 15 ]. These findings signify clearly that an attempt to extensively skeletonise the cystic duct during routine laparoscopic cholecystectomy is an unnecessary step and even potentially hazardous for the patient, particularly when the operation is not performed by surgeons with hepatobiliary expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection of the cystic duct remnant has been the traditional approach for treatment of cystic duct remnant syndromes 2 . We report a case of cystic duct stump syndrome (stumpitis) managed solely with endoscopy.…”
Section: Figmentioning
confidence: 99%
“…On 4-week follow-up, the patient confirmed complete resolution of symptoms. Surgical resection of the cystic duct remnant has been the traditional approach for treatment of cystic duct remnant syndromes [2]. We report a case of cystic duct stump syndrome (stumpitis) mana-▶ Fig.…”
mentioning
confidence: 95%